In-Vitro Fertilization Protocols: Agonist versus Antagonist in Relation to Ovarian Response, Embryological Performance, and Treatment Characteristics (Medical Forum Monthly, 2026)
Objective: To compare the characteristics of ovarian stimulation, oocyte maturation, embryo development, and transfer-related parameters between the gonadotropin-releasing hormone agonist long protocol and the gonadotropin-releasing hormone antagonist protocol in infertile couples having intracytoplasmic sperm injection.Study Design: Retrospective comparison analysisPlace and Duration of Study: This study was conducted at the Department of Gynecology & Obstetrics, Collage of Pharmacy, University of Duhok from 20th August 2024 to 28th February 2025.Methods: This retrospective comparison analysis was performed on 200 Intracytoplasmic sperm injection cycles utilising either a gonadotropin-releasing hormone agonist or gonadotropin-releasing hormone antagonist regimen. We looked at the length of stimulation, the amount of gonadotropin used, the reaction of the ovaries, the age of the oocytes, the success of fertilisation, the quality of the embryos, the thickness of the endometrium, and the day of embryo transfer.Results: The gonadotropin-releasing hormone antagonist protocol correlated with markedly reduced stimulation days (p=0.003) and diminished gonadotropin requirements (p<0.001). The ovarian response was more effective in antagonist cycles, with increased quantities of metaphase II oocytes (p=0.001) and fertilised oocytes (p=0.010). Thequality of embryos varied considerably among procedures (p < 0.001), with antagonist cycles yielding a greater percentage of high-grade blastocysts and more frequent day-5 embryo transfers (p<0.001). The endometrialthickness on the day of embryo transfer was considerably higher in antagonist cycles (p=0.032).Conclusion: Gonadotropin-releasing hormone antagonist programs exhibit enhanced stimulation efficacy and embryological outcomes relative to gonadotropin-releasing hormone agonist protocols. These data indicate that biological and treatment-related benefits linked to antagonist regimens may enhance reproductive outcomes.